Perancangan RPL Berbasis Blockchain untuk Audit Otomatis Transparan dalam Kolaborasi Tim Remote - Muhammad Yunus Rangkuti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The shift toward remote work in software engineering has introduced critical challenges in transparency, integrity, and auditability of development activities. Although version control systems like Git have become standard tools for tracking development history, they remain vulnerable to data manipulation, deletion of contribution records, and inefficiencies in conducting independent, real-time audits. This study proposes a blockchain-based software engineering system designed to address these issues. The system automatically records all key development activities—including commits, merges, pull requests, and branches—through integration with smart contracts running on the Hyperledger Fabric platform. Activity data is encrypted into hash values and stored on a distributed, tamper-proof ledger. A case study was conducted involving two remote development teams in Indonesia over a two-month real-world project cycle. Evaluation results show a significant improvement in audit efficiency, reducing average audit time from 48 hours to less than 6 hours, along with a 30% increase in perceived trust among team members. This research contributes a practical and technically validated approach to software development auditing in remote collaboration contexts, while also demonstrating the functional extension of blockchain technology beyond financial domains into software engineering practices.